2014
DOI: 10.4238/2014.june.9.15
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of resistance to powdery mildew at the early stage of development in wheat line N0308

Abstract: ABSTRACT. Powdery mildew, caused by Blumeria graminis f. sp tritici (Bgt) is one of the devastating diseases of wheat and causes yield losses in temperate wheat growing regions. A wheat line, N0308 with resistance to powdery mildew was used in this study. A suppression subtractive hybridization cDNA library was constructed from the wheat leaves inoculated by Bgt at the two-leaf stage. The differentially expressed genes in response to Bgt infection in wheat were identified, and a total of 175 positive clones fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
7
1
Order By: Relevance
“…From 12 SSH libraries, we identified 304 gene sequences in which 23% were ESTs. The percentage was less than that in previous reports [ 21 , 22 ], which might be attributed that in this study we used inbred gerbils with high genetic consistency. Most of the identified genes were associated with proliferation, differentiation, migration, and apoptosis, all of which may influence vascular development.…”
Section: Discussioncontrasting
confidence: 63%
“…From 12 SSH libraries, we identified 304 gene sequences in which 23% were ESTs. The percentage was less than that in previous reports [ 21 , 22 ], which might be attributed that in this study we used inbred gerbils with high genetic consistency. Most of the identified genes were associated with proliferation, differentiation, migration, and apoptosis, all of which may influence vascular development.…”
Section: Discussioncontrasting
confidence: 63%
“…Security of wheat production is of great economic importance globally as it is a key staple food crop. Wheat cultivation can be found in many areas of the world, particularly in regions with maritime and semicontinental climates, and this diversity presents multiple constraints on productivity (Alam et al , 2014). Despite the growing scarcity of arable land and shifting of agriculture to more marginal lands, the production volume of wheat is projected to increase (Peng et al , 2011; Placido et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PM disease resistance has been reported in cucumber, wheat, and grapevine (Zhou et al, 2013;Alam et al, 2014;Lu et al, 2014;Zhang et al, 2014). In strawberry (Fragaria x ananassa Duchesne), cleaved amplified polymorphic sequence markers related to PM resistance have been developed (Heejeong et al, 2015), and interactions between strawberry and PM have been revealed using the RNA-seq method (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%